POTENSI DAN KANDUNGAN LOGAM BERAT TEMBAGA (Cu) dan BESI (Fe) pada KERANG DARAH (Anadara granosa) di KABUPATEN NUNUKAN - Heppi Iromo (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2010)
The purpose of this Research is to investigate heavy metal content in meet darah shell (Anadara granosa). Method to collecting of primary data is method survey with direct interview technique and analysed in laboratory. It were analysed heavy metal such as; Fe, and Cu, by used AAS. The result test laboratory for darah shell (Anadara granosa) with AAS is it can consumed because it have not contain dangerous heavy metal like Cu but it detected contain little heavy metal Fe. Key Words: Darah shell, Heavy metal Fe and Cu.